Characterization and high-throughput screening of the polymyxin resistance enzyme MCR-1 - Sieron, Arthur (My University, 2017)
Polymyxins are potent antibiotics that bind to the outer membrane of Gram-negative bacteria, entering the cell and disrupting the inner membrane, resulting in cell death. They were traditionally used as antibiotics of last resort, but the recent surge of multidrug resistant pathogens has renewed interest in these antibiotics. The emergence of polymyxin resistance determinants such as the recently discovered plasmid-mediated phosphoethanolamine transferase MCR-1 may put a strain on the future effectiveness of this antibiotic. One method to combat the rise in antibiotic resistant bacteria is through the identification and development of antibiotic adjuvants. These are small molecules that are able to inhibit the resistance mechanism, allowing previously ineffective antibiotics to once again become effective at treating bacterial infections. In this work, a high throughput cell-based screen was conducted using an in-house library of Actinomycete-derived crude cell extracts in order to search for a natural product inhibitor of an E. coli strain expressing mcr-1. In addition, the development of a new enzyme assay was attempted using purified MCR-1 C-terminal catalytic domain and a chromogenic substrate to test enzymatic activity in vitro, in hopes of establishing a simple means of studying inhibition of MCR-1. The structure-function relationship of MCR-1 was also explored by generating amino acid substitutions and studying their effect on the ability of the enzyme to confer resistance to colistin, as well as the generation of MCR-1 transmembrane truncation mutants to determine if it was possible to generate a shorter variant of MCR-1 that retained its enzymatic activity. This work furthers our understanding of the biochemistry and enzymology of MCR-1, and outlines attempts to identify inhibitors of MCR-1 in order to re-sensitize resistant bacteria to polymyxins.
Keywords: antibiotic resistance; polymyxin; colistin; MCR-1; Escherichia coli; Gram-negative; antibiotic adjuvant; antibiotic resistance platform; high throughput screening; natural products